Chitosan nanocomposites with CdSe/ZnS quantum dots and porphyrin. Issue 2 (4th January 2022) - Sewid, F. A.; Annas, K. I.; Dubavik, A.; Veniaminov, A. V.; Maslov, V. G.; Orlova, A. O.
Abstract : A CdSe/ZnS QD-TPP nanocomposite and energy transfer from QDs to (i) TPP monomers to oxygen generating singlet oxygen (SO) and (ii) TPP aggregates cannot generate SO in chitosan solution. Abstract : Water-soluble nanocomposites based on CdSe/ZnS quantum dots (QDs) and hydrophobic tetraphenylporphyrin (TPP) molecules passivated by chitosan (CS) have been formed. Magnetic circular dichroism (MCD) spectra evidence TPP presence in both monomeric and agglomerated forms in the nanocomposites. The nanocomposites demonstrate more pronounced singlet oxygen generation compared to free TPP in CS at the same concentration due to the intracomplex Förster resonance energy transfer (FRET) with a 45% average efficiency.